2014
DOI: 10.4183/aeb.2014.545
|View full text |Cite
|
Sign up to set email alerts
|

Catecholamines Increase in Vitro Proliferation of Murine B16F10 Melanoma Cells

Abstract: Context.Melanoma is the most aggressive skin cancer, with significant morbidity and mortality, and one factor that may influence the course of disease is stress.Objective. Our aim was to evaluate the effect of corticosterone, norepinephrine, epinephrine on murine B16F10 melanoma cells in vitro proliferation.Methods. B16F10 melanoma cells were treated with different concentrations of tested hormones. The proliferative capacity of melanoma cells was quantified by MTS assay and the cell viability was quantified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 54 publications
0
32
0
Order By: Relevance
“…Given these findings, adiponectin emerges as a target molecule for reducing the risk of metabolic syndrome, type 2 diabetes mellitus and atherosclerotic disease. Research is currently conducted to determine the measures, pharmacological or non-pharmacological, that may increase the circulating levels of adiponectin (19,(36)(37)(38). Physical effort appears to be associated with an increase in serum adiponectin levels; one week of aerobic exercise was reported to lead to a significant increase in adiponectin in obese men (39).…”
Section: Discussionmentioning
confidence: 99%
“…Given these findings, adiponectin emerges as a target molecule for reducing the risk of metabolic syndrome, type 2 diabetes mellitus and atherosclerotic disease. Research is currently conducted to determine the measures, pharmacological or non-pharmacological, that may increase the circulating levels of adiponectin (19,(36)(37)(38). Physical effort appears to be associated with an increase in serum adiponectin levels; one week of aerobic exercise was reported to lead to a significant increase in adiponectin in obese men (39).…”
Section: Discussionmentioning
confidence: 99%
“…The formation of excess dopaquinone leads to the neural disorder and death (49). Thus, it is suggested the involvement of the tyrosinase in the neuro-degeneration associated to the Parkinson disease (50) and Huntington chorea (51,52). Together with the tyrosinase, in the transformation of the tyrosine in melanic pigments, 2 more proteins are involved, named dopachrometautomerasis, represented by the protein 1 related to the tyrosine (TRP-1) and protein 2 related to the tyrosine (TRP-2).…”
Section: Synthesis Of the Melanic Pigmentsmentioning
confidence: 99%
“…Many studies on BM in melanoma are focused on identifying the gene expression or metabolic profile that are associated with an increased risk of brain secondary tumor formation and that can be used as predictive biomarkers of disease progression (22)(23)(24)(25)(26). Nieder et al suggested that a combination of Karnofsky performance status (KPS) and serum lactate dehydrogenase (LDH) level significantly predicted survival in BM patients (27).…”
Section: Biomarkers In Melanoma Brain Metastasis Predictionmentioning
confidence: 99%